Arctic Environmental Test of Rations - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The object of the procedures outlined in the Materiel Test Procedure is to provide a means of evaluating the acceptability of rations in arctic winter environmental conditions.